An Observational Study of Regulatory Violations Related to Online Tobacco Product Marketing and Retailer Responses to US FDA Warning Letters - Dorie E. Apollonio; Cathi E. Dennehy; Candy Tsourounis; Tanner Wakefield (SAGE Publishing, 2024)
Background Marketing of flavored tobacco products has drawn concern because they are used disproportionately by young people. Online retailers have marketed e-cigarette liquids and devices to minors despite knowing it is illegal. The onset of the COVID-19 pandemic resulted in substantial increases in online purchasing, however, there has been limited study of possible shifts in online tobacco product marketing associated with this change. Objectives We sought to identify types of tobacco regulatory violations in 2021-2022, marketing claims made by retailers, the extent to which retailers had processes in place to deter minors from browsing websites, and the types of flavors promoted. Design and Methods Our observational study was based on an initial sample of 100 tobacco retailers that had received FDA Warning Letters in 2020-2021. Using methods validated in previous research, we coded the letters for retailer information, violation type, and for retailers with an online presence, the types of products sold, and their marketing claims. Results Most retailers with violations were in the US South (48%), 65% had an online presence at the time of analysis, and 53% had a website that offered online product sales. The most common type of violation was the sale of new tobacco products without required marketing authorization (83%). For the retailers in the sample with active websites, 42% were still selling a product that the FDA had indicated was marketed unlawfully. Among these retailers with active websites, 32% did not have processes in place to deter access by minors. Advertised flavors focused on food (eg, mango, honey) and concepts (eg, "love", "classic"). Conclusions Online retailers appeared less likely to remediate tobacco product violations identified by the FDA after the onset of the COVID-19 pandemic than before it, and few websites had strong processes in place that would deter youth browsing.